Prunin attenuates aflatoxin B1-induced testicular toxicity by alleviating oxidative stress and modulating TLR4/MyD88/NF-κB and Bax/Bcl-2/Caspase-3 signaling pathways - Muhammad Umar Ijaz; Ghulam Mustafa; Muhammad Zaid Salar; Amjad Islam Aqib; Ghulam Hussain; Aisha Khatoon; Hamida Hamdi (Tissue and Cell, 2027)

Exome sequencing of pashtun familial epilepsy in Pakistan reveals novel variants in LAMA5, KCNQ2 and GNAO1 - Qaisar Ali; Sadiq Azam; Jamila Javed; Muhammad Zaheer; Saqib Ullah; Aqib Iqbal; Ibrar Khan; Shoaib Ur Rehman (Molecular Biology Reports, 2026)

Supplementing the diet of Damani ewes with fermented olive pomace increases nutrient digestibility and milk yield, and improves their metabolic status - Ihtisham ul Haq; Muhammad Aqib; Muhammad Tahir Khan; Yong Liu; Hangshu Xin; Nazir Ahmad Khan (Small Ruminant Research, 2026)

Clove oil in combination with flurbiprofen attenuated imiquimod-induced psoriasis-like skin inflammation in a mouse model: A mechanistic study - Qianqian Xing; Shuaijie Wang; Hafiz Muhammad Zubair; Aqib Mustafa; Atiq-Ur-Rehman; Hafiza Sidra Yaseen; Farzana Andleeb; Muhammad Asif; Ning Guan (Inflammopharmacology, 2026)

Design and development of a low-cost industrial prototype of spot-specific spraying system for potato weed detection using deep learning - Faiza Khan; Muhammad Naveed Tahir; Muhammad Aqib; Yubin Lan; Noureen Zafar; Shoaib Saleem; Zainab Haroon; Wenjiang Huang (Computers and Electronics in Agriculture, 2026)

A population model with fear effect: detailed dynamics in a stochastic and deterministic environment - Muhammad Aqib Abbasi; Rizwan Niaz; Mansour Almazroui; Rabin Chakrabortty; Salah Knani; Mohamed Abdelghany Elkotb (Stochastic Environmental Research and Risk Assessment, 2026)

Correction: Modulation of inflammatory and oxidative stress pathways by ethanolic extract of Suaeda fruticosa Forssk. Ex J.F.Gmel in animal models of ulcerative colitis - Juan Liu; Aqib Mustafa; Muhammad Fiaz; Hafiz Muhammad Zubair; Tahir Maqbool; Atiq ur Rehman; Muhammad Asif; Jing Yang (Inflammopharmacology, 2026)

Modulation of inflammatory and oxidative stress pathways by ethanolic extract of Suaeda fruticosa Forssk. Ex J.F.Gmel in animal models of ulcerative colitis - Juan Liu; Aqib Mustafa; Muhammad Fiaz; Hafiz Muhammad Zubair; Tahir Maqbool; Atiq ur Rehman; Muhammad Asif; Jing Yang (Inflammopharmacology, 2026)

Integrated energy and thermal analysis for residential buildings in karachi: A comprehensive audit approach - Shahzaib Hassan; Saqlain Abbas; Zahid Hussain; Ahmad Asim; Zulkarnain Abbas; Muhammad Aqib (Next Research, 2026)

Biochar and plant growth-promoting rhizobacteria: a promising combination enhancing wheat (Triticum aestivum L.) growth under chromium stress - Fazal Jalal; Awais Ahmad; Aqib Iqbal; Zafar Hayat Khan; Shah Fahad; Nazia Tahir; Fazal Said; Muhammad Imtiaz; Muhammad Ali Khan; Sayed Hussain; Attaur Rahman; Wasim Khan; et al. (Rhizosphere, 2025)

Ameliorating CO₂ capture performance of PEI/PES hybrid membranes via integration of zeolitic imidazolate frameworks - Sadia Sagar; Aqib Riaz; Farzana Siddique; Aysha Siddiqa; Mohsin Ali; Mahnoor Asif; Muhammad Waqas Iqbal; Fawad Inam (Journal of Environmental Chemical Engineering, 2025)

Double layer stratifications of Carreau Yasuda fluid flow in cylindrical system along with activation energy - T. Salahuddin; Aqib Ali; Muhammad Awais; Mair Khan; Nissren Tamam; Nidhal Ben Khedher (Dynamics of Atmospheres and Oceans, 2025)

Molecular Epidemiology and Resistant Gene Mapping of Bacterial Isolates from Houbara bustards - Maham Fatima; Tasleem Kausar; Amjad Islam Aqib; Muhammad Shoaib; Farid S. Ataya; Mohamed Saad Daoud (Current Microbiology, 2025)

Turn-off Fluorimetric Detection of Fe3+ Metal Ions by a Schiff Base Probe (E)-2-(((2-hydroxy-4-sulfonaphthalen-1-yl) imino) methyl) Benzoic Acid: A Combined Experimental and Theoretical Study - Muhammad Shahbaz; Muhammad Aqib Khurshid; Muhammad Ejaz; Mazhar Amjad Gilani; Maham Saeed; Ayesha Shahzad; Sundas Shahzad; Rashid Masih; Shahzad Sharif (Journal of Fluorescence, 2025)

Simulation-based assessment of the impact of conservation tillage and strip intercropping on soil microbial biomass carbon - Sana ur Rehman; Xiaoping Xin; Shahzada Sohail Ijaz; Shroz Fatima; Ayesha Siddiqa; Hayder Bin Khalid; Imran Haider; Rashid Iqbal; Aqib Mahmood; Sajad Hussain; Atta Mohi Ud Din; Taqi Raza; et al. (CATENA, 2025)

Image segmentation and machine learning modelling for water status determination and precision irrigation management - Hamza Salah Ud Din; Aqib Iqbal; Fazal Jalal; Awais Ahmad; Muhammad Haris Paracha; Shah Fahad; Zafar Hayat Khan; Shah Saud; Taufiq Nawaz (Journal of Crop Science and Biotechnology, 2025)

Enhanced Photocatalytic Degradation of Methyl Red Dye with Bismuth-Doped ZnO: Kinetics, Mechanistic and Re-cyclability Aspects - Muhammad Alamzeb; Noor-ul-Ain Zulfiqar; Muhammad Faran Akhtar; Iqra Riaz; Faiza Ameen; Aqib Asghar; William N. Setzer (Journal of Fluorescence, 2025)

Dynamical analysis of an ecological model with prey refuge and Beddington–DeAngelis functional response - Muhammad Aqib Abbasi; Rizwan Niaz; Olayan Albalawi; Hadil Alhazmi; Hamiden Abd El-Wahed Khalifa (Stochastic Environmental Research and Risk Assessment, 2025)

Correction: Multivariate and Association Analyses of Various Seed Yield Contributing Traits Divulge Genetic Diversity Among Pisum sativum L. Genotypes - Noshi Parveen; Shamim Umer; Changwei Tan; Abdul Jabbar; Bilqees Kanwal; Imran Haider; Waqas Raza; Anwer Usma; Aqib Mahmood; Muhammad Bilawal Junaid; Salman Haidar Abbasi; Alanoud T. Alfagham; et al. (Plant Molecular Biology Reporter, 2025)

Multivariate and Association Analyses of Various Seed Yield Contributing Traits Divulge Genetic Diversity Among Pisum sativum L. Genotypes - Noshi Parveen; Shamim Umer; Changwei Tan; Abdul Jabbar; Bilqees Kanwal; Imran Haider; Waqas Raza; Anwer Usma; Aqib Mahmood; Muhammad Bilawal Junaid; Salman Haidar Abbasi; Alanoud T. Alfagham; et al. (Plant Molecular Biology Reporter, 2025)

Sustainable immobilization strategy for Desertifilum tharense BERC-3 on corncobs to enhance biomass production and high-value metabolites - Muhammad Usman; Md Asraful Alam; Ayesha Shahid; Zhang Beixiao; Aqib Zafar Khan; Anqi Zhao; A.E. Solovchenko; Muhammad Aamer Mehmood; Xu Jingliang (Journal of Environmental Chemical Engineering, 2025)

Genotypic Profiling, Functional Analysis, Cholesterol-Lowering Ability, and Angiotensin I-Converting Enzyme (ACE) Inhibitory Activity of Probiotic Lactiplantibacillus plantarum K25 via Different Approaches - Tariq Aziz; Hu Hangyu; Muhammad Naveed; Muhammad Aqib Shabbir; Abid Sarwar; Jasra Nasbeeb; Yang Zhennai; Metab Alharbi (Probiotics and Antimicrobial Proteins, 2025)

Revealing Lactiplantibacillus Plantarum K25 Derived (Z)-18-Octadec-9-Enolide in Modulating Aquaporin-8 in Colorectal Cancer by Bridging the Gut Microbiome and Membrane Biology - Tariq Aziz; Muhammad Aqib Shabbir; Abid Sarwar; Zhennai Yang; Lin Lin; Wafa Abdullah I. Al-Megrin; Ashwag Shami; Maher S. Alwethaynani; Areej A Alhhazmi; Fahad Al-Asmari; Fakhria A. Al-Joufi; Deema Fallatah (Cell Biochemistry and Biophysics, 2025)

Development and in vitro tuning of empagliflozin-containing dissolvable microneedle patch for enhanced transdermal delivery - Aqib Javed; Rai Muhammad Sarfraz; Asif Mahmood; Zulcaif Ahmad; Muhammad Rouf Akram; Hira Ijaz; Shammas Ali; Anam Shahzadi (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Physicochemical, Enzymatic, and Microbial Responses to Phosphofructokinase Overexpressing Transgenic Potato Cultivation: A Pot Experiment - Muhammad Junaid Sadiq Gill; Umer Ali; Aqib Hassan Ali Khan; Ismat Nawaz; Tayyab Ashfaq Butt; Cyrus Raza Mirza; Ameena Iqbal; Arfan Ali; Faiz Ur Rahman; Sohail Yousaf; Mazhar Iqbal (American Journal of Potato Research, 2025)

Yield gains and resource use advantages driven by legume choice and row ratio in cotton/legume intercropping under arid-irrigated conditions - Muhammad Ali Raza; Atta Mohi Ud Din; Hassan Shehryar Yasin; Hina Gul; Amjad Saeed; Aqib Mehmood; Sana Ur Rehman; Zafar Iqbal; Rashid Iqbal; Noorah Al Kubaisi; Mohamed S. Elshikh; Ghulam Abbas Shah; et al. (Field Crops Research, 2025)

Investigating co-dimension one and two bifurcations in a discrete-time epidemic model with vaccination and vital dynamics - Muhammad Aqib Abbasia; Maria Samreena; Ekrem Savasb; J. F. Gómez-Aguilarc (Modeling Earth Systems and Environment, 2025)

In-vitro and in-vivo assessments of greenly synthesized iron oxide nanoparticles from Cascabela thevetia plant extract for the treatment of ventricular septal defect - Amina Abid; Muhammad Naveed; Tariq Aziz; Muhammad Aqib Shabbir; Hira Mubeen; Ayaz Ali Khan; Abdullah F Alsmari (South African Journal of Botany, 2025)

Integration of physio-biological methods for remediation of dyes and toxic metals from textile wastewater - Muhammad Ayaz; Aqib Hassan Ali Khan; Kang Song; Asmat Ali; Sohail Yousaf; Abeer Kazmi; Abdur Rashid (Bioresource Technology Reports, 2025)

Effective synergism of Moringa oleifera with antibiotics, body growth, and decoction replacement - Qandeel Ashraf; Amjad Islam Aqib; Hamid Majeed; Shahbaz Ul Haq; Muhammad Farrukh Nisar; Muhammad Usman; Afshan Muneer; Saba Batool; Farid S. Ataya (South African Journal of Botany, 2024)

Dairy farm waste: A potential reservoir of diverse antibiotic resistance and virulence genes in aminoglycoside- and beta-lactam-resistant Escherichia coli in Gansu Province, China - Muhammad Shoaib; Minjia Tang; Amjad Islam Aqib; Xuejing Zhang; Zhongyong Wu; Yang Wen; Xiao Hou; Jinpeng Xu; Ruochen Hao; Shengyi Wang; Wanxia Pu (Environmental Research, 2024)

Synergistic biochar and Serratia marcescens tackle toxic metal contamination: A multifaceted machine learning approach - Hamid Rehman; Aqib Hassan Ali Khan; Tayyab Ashfaq Butt; Muhammad Toqeer; Muhammad Bilal; Mahtab Ahmad; Ahmed Abdullah Alawi Al-Naghi; Enamur Rahim Latifee; Omar Ali Saad Algassem; Mazhar Iqbal (Journal of Environmental Management, 2024)

Synthesis, Crystal Structure and Fluorimetric Study of 2-phenylphthalazin-1(2H)-one: a Highly Selective Florescent Chemosensor for Detection of Fe3+ and Fe2+ Metal Ions - Shahzad Sharif; Muhammad Shahbaz; Onur Şahin; Muhammad Aqib Khurshid; Maryam Musaffa Anbar; Birra Dar (Journal of Fluorescence, 2024)

Improving environmental and economic sustainability of cutlery manufacturing in a developing nation through energy reduction and energy transition initiatives - Muhammad Aqib; Shamraiz Ahmad; Shahid Ikramullah Butt (Environmental Science and Pollution Research, 2024)

Sustainability and photocatalytic performance of MOFs: Synthesis strategies and structural insights - Zeshan Ali Sandhu; Umme Farwa; Muhammad Danish; Muhammad Asam Raza; Aqib Talib; Hifza Amjad; Rukhmah Riaz; Abdullah G. Al-Sehemi (Journal of Cleaner Production, 2024)

Emerging trends in algae farming on non-arable lands for resource reclamation, recycling, and mitigation of climate change-driven food security challenges - Fatima Tahir; Hira Ashfaq; Aqib Zafar Khan; Mahwish Amin; Iqra Akbar; Hafiza Aroosa Malik; Mohammed Abdullah; Abdulrahman H. Alessa; Ahmad A. Alsaigh; Peter J. Ralph; Muhammad Aamer Mehmood; Sana Malik (Reviews in Environmental Science and Bio/Technology, 2024)

A novel integrated approach employing Desertifilum tharense BERC-3 for efficient wastewater valorization and recycling for developing peri-urban algae farming system - Muhammad Usman; Aqib Zafar Khan; Sana Malik; Wenlong Xiong; Yongkun Lv; Shen Zhang; Anqi Zhao; A.E. Solovchenko; Md Asraful Alam; Abdulrahman H. Alessa; Muhammad Aamer Mehmood; Jingliang Xu (Chemosphere, 2024)

Biopesticides: Uses and importance in insect pest control: A review - Babu Saddam; Muhammad Aqib Idrees; Pawan Kumar; Mohammad Mahamood (International Journal of Tropical Insect Science, 2024)

Wastewater-Grown Algal Biomass as Carbon-neutral, Renewable, and Low Water Footprint Feedstock for Clean Energy and Bioplastics - Muhammad Aamer Mehmood; Mahwish Amin; Muhammad Nabeel Haider; Sana Malik; Hafiza Aroosa Malik; Md. Asraful Alam; Jingliang Xu; Abdulrahman H. Alessa; Aqib Zafar Khan; Raj Boopathy (Current Pollution Reports, 2024)

Genome-wide association study reveals novel genes on different chromosomal positions regulating boll weight in upland cotton (Gossypium hirsutum L.) - Zubair Iqbal; Muhammad Shahid Iqbal; Salman Alamery; Khurram Shehzad; Qamar U. Zaman; Safira Attacha; Zareen Sarfraz; Mian Faisal Nazir; Daowu Hu; Muhammad Mubashar Zafar; Aqib Zeb; Shoupuhe; et al. (Genetic Resources and Crop Evolution, 2024)

A comprehensive review: persistence, circulative transmission of begomovirus by whitefly vectors - Muhammad Aqib Idrees; Arzlan Abbas; Babu Saddam; Muhammad Hamid Bashir; Hassan Naveed; Ahmad Kamran Khan; Muhammad Zulqar Nain Dara (International Journal of Tropical Insect Science, 2024)

Effect of crop combination on yield performance, nutrient uptake, and land use advantage of cereal/legume intercropping systems - Muhammad Ali Raza; Wang Zhiqi; Hassan Shehryar Yasin; Hina Gul; Ruijun Qin; Sana Ur Rehman; Aqib Mahmood; Zafar Iqbal; Zaheer Ahmed; Shuanglong Luo; Chen Juan; Xue Liang; et al. (Field Crops Research, 2023)

Introducing new green machining technology to enhance process performance and reduce environmental pollution in the metal processing industry - Pengwen Wang; Aqib Mashood Khan; Mohammed Alkahtani; Fahad Alasim; Muhammad Jamil; Ghulam Hussain (Environmental Science and Pollution Research, 2023)

Natural and artificial green infrastructure (GI) for sustainable resilient cities: A scientometric analysis - Aqib Zahoor; Tao Xu; Miao Wang; Muhammad Dawood; Sandylove Afrane; Ying Li; Jian Lin Chen; Guozhu Mao (Environmental Impact Assessment Review, 2023)

Bioenergy potential of Saccharum bengalense through pyrolysis, reaction kinetics, TG-FTIR-GCMS analysis of pyrolysis products, and validation of the pyrolysis data through machine learning - Azeem Asghar; Chen-Guang Liu; Imtiaz Ali; Aqib Zafar Khan; Hui Zhu; Ning Wang; Muhammad Nawaz; Tanveer A. Tabish; Muhammad Aamer Mehmood; Raqiqa Tur Rasool (Chemical Engineering Journal, 2023)

Detrimental effects of Cd and temperature on rice and functions of microbial community in paddy soils - Raheel Munir; Mehmood Jan; Sajid Muhammad; Muhammad Afzal; Nazia Jan; Muhammad Umair Yasin; Iqbal Munir; Aqib Iqbal; Shuaiqi Yang; Weijun Zhou; Yinbo Gan (Environmental Pollution, 2023)

Impact of seasons and wastewater cultivation on the biomass and biodiesel production by the Plectonema terebrans BERC10 as a candidate for a multiproduct algal biorefinery - Muhammad Nabeel Haider; Aqib Zafar Khan; Muhammad Usman; Deepanraj Balakrishnan; Muhammad Rizwan Javed; Sana Malik; Chen-Guang Liu; Muhammad Aamer Mehmood; Ghulam Abbas Ashraf (Fuel, 2023)

Biological and Photocatalytic Degradation of Congo Red, a Diazo Sulfonated Substituted Dye: a Review - Rana Rashad Mahmood Khan; Hoorish Qamar; Ayesha Hameed; Aqmar ur Rehman; Muhammad Pervaiz; Zohaib Saeed; Aqib Adnan; Ayoub Rashid Ch (Water, Air, & Soil Pollution, 2022)

Soil conditioners improve rhizodegradation of aged petroleum hydrocarbons and enhance the growth of Lolium multiflorum - Fida Hussain; Aqib Hassan Ali Khan; Imran Hussain; Asifa Farooqi; Yousaf Shad Muhammad; Mazhar Iqbal; Muhammad Arslan; Sohail Yousaf (Environmental Science and Pollution Research, 2022)

Advances in Green Technologies for the Removal of Effluent Organic Matter from the Urban Wastewater - Ayesha Shahid; Aqib Zafar Khan; Sana Malik; Chen-Guang Liu; Muhammad Aamer Mehmood; Achmad Syafiuddin; Ning Wang; Hui Zhu; Raj Boopathy (Current Pollution Reports, 2021)

Clove (Syzygium aromaticum) and its phytochemicals in ruminant feed: an updated review - Muhammad Saeed; Muhammad S. Khan; Mahmoud Alagawany; Mayada R. Farag; Othman Alqaisi; Amjad I. Aqib; Muhammad Qumar; Faisal Siddique; Mohamed Fawzy Ramadan (Rendiconti Lincei. Scienze Fisiche e Naturali, 2021)

Physiological insights into sulfate and selenium interaction to improve drought tolerance in mung bean - Muhammad Aqib; Fahim Nawaz; Sadia Majeed; Abdul Ghaffar; Khawaja Shafique Ahmad; Muhammad Asif Shehzad; Muhammad Naeem Tahir; Muhammad Aurangzaib; Hafiz Muhammad Rashad Javeed; Muhammad Habib-ur-Rahman; Muhammad Munir Usmani (Physiology and Molecular Biology of Plants, 2021)
The present study involved two pot experiments to investigate the response of mung bean to the individual or combined SO 4 2− and selenate application under drought stress. A marked increment in biomass and NPK accumulation was recorded in mung bean seedlings fertilized with various SO 4 2− sources, except for CuSO 4 . Compared to other SO 4 2− fertilizers, ZnSO 4 application resulted in the highest increase in growth attributes and shoot nutrient content. Further, the combined S and Se application (S + Se) significantly enhanced relative water content (16%), SPAD value (72%), photosynthetic rate (80%) and activities of catalase (79%), guaiacol peroxidase (53%) and superoxide dismutase (58%) in the leaves of water-stressed mung bean plants. Consequently, the grain yield of mung bean was markedly increased by 105% under water stress conditions. Furthermore, S + Se application considerably increased the concentrations of P (47%), K (75%), S (80%), Zn (160%), and Fe (15%) in mung bean seeds under drought stress conditions. These findings indicate that S + Se application potentially increases the nutritional quality of grain legumes by stimulating photosynthetic apparatus and antioxidative machinery under water deficit conditions. Our results could provide the basis for further experiments on cross-talk between S and Se regulatory pathways to improve the nutritional quality of food crops.

Enhanced uptake of Cd, Cr, and Cu in Catharanthus roseus (L.) G.Don by Bacillus cereus: application of moss and compost to reduce metal availability - Muhammad Umair Mushtaq; Ameena Iqbal; Ismat Nawaz; Cyrus Raza Mirza; Sohail Yousaf; Ghazanfar Farooq; Muhammad Arif Ali; Aqib Hassan Ali Khan; Mazhar Iqbal (Environmental Science and Pollution Research, 2020)

Influence of Pseudomonas japonica and organic amendments on the growth and metal tolerance of Celosia argentea L. - Ameena Iqbal; Muhammad Umair Mushtaq; Aqib Hassan Ali Khan; Ismat Nawaz; Sohail Yousaf; Zeshan; Mazhar Iqbal (Environmental Science and Pollution Research, 2020)

Molecular epidemiology of bovine anaplasmosis in Khyber Pakhtunkhwa, Pakistan - Shahid Hussain Farooqi; Muhammad Ijaz; Muhammad Imran Rashid; H. Nabi; S. Islam; Amjad Islam Aqib; Kashif Hussain; Amjad Khan; Syeda Nayab Batool Rizvi; Shakeel Mahmood; Khalid Mehmood; Hui Zhang (Tropical Animal Health and Production, 2018)

Osmoregulation and antioxidant production in maize under combined cadmium and arsenic stress - Shakeel Ahmad Anjum; Mohsin Tanveer; Saddam Hussain; Babar Shahzad; Umair Ashraf; Shah Fahad; Waseem Hassan; Saad Jan; Imran Khan; Muhammad Farrukh Saleem; Ali Ahsan Bajwa; Longchang Wang; et al. (Environmental Science and Pollution Research, 2016)